Kinetics Study of Sewage Sludge Treatment by Anaerobic Digestion - Nour, Abdurahman Hamid (2000)
This study was carried out to evaluate the applicability of three known kinetics models (Monod, Contois and Chen and Hashimoto), overall microbial kinetics, as well as to experimentally assess the influence of the organic loading rates and retention times on kinetic models. To accomplish the objectives of this study, a 50 litre laboratory scaled membrane anaerobic system (MAS) combining ultrafiltration (UP) membrane with anaerobic reactor was used to treat raw sewage sludge, which collected from Taman Tun Dr. Ismail, sewage treatment plant (T.T.Dr.Ismail). Six steady states were attained as a part of a kinetic study. The results of all SIX . steady states were successfully fitted, above 98%, by Monod, Contois, and Chen and Hashimoto models. Contois model appeared to be the best at 99.7%. The microbial kinetic constants were Y = 0.74 gVSS/gCOD and b = 0.20 day-I. The minimum solids retention time, Be min obtained from the three kinetic models ranged from 5-16.9 days. The total gas yield obtained ranged from 0.28 VgCOD/d to 0.81 VgCOD/d at organic loading rate (OLR) of between 0.1kgCOD/m3.d to 10 kgCOD/m3d. The solids retention time (SRT) decreased from 1250 days to 16.1 days, (from SSI to SS6). The composition of methane gas, CH4 varied from 66.3% to 76.3%. At CH4, 66.3%, the solids retention time and hydraulic retention time were found to be 16.1 day and 7.8 days, with the COD removal efficiency range of between 96.5 - 99 % as well as high solids retention time 8c• The range of mixed liquor suspended solids was from 12760 mg/l to 21800 mg/l. The two methods of membrane cleaning (Mild brushing , flush with water and soak membrane in 0.1 M NaOH for day), were very important in order to increase the permeate flux and flowrate. The flux recovery time was 15 to 18 days. The maximum and minimum level of the flux were found to be 62. 1 Vm2 /hr and 6.9 Vm2/hr respectively.